The effects of creatine supplementation on kidney function - Silva, Filipe Gomes da (2023)
Study this topic because it understands the importance of supplementation and how applicable in this way to the human organism, an overload of the renal system is extremely harmful to the patient, as well as an extremely important evaluation for the process of this process to be alternative in a safe way. To discuss the effects of creatine supplementation on patients' renal function. This is a literature review carried out in the SciELO, LILASCS, Institutional Repository databases. The articles were selected based on the literature published between 2014-2021 and applying inclusion and exclusion criteria. The analyzed results were studied to develop the function of nutritional monitoring for the guidance of renal function, since the function created for the functioning of the organism is fundamental for the functioning of the human organism. It is concluded that the nutritional process for creatine gain in the body can occur in two ways: through supplementation with guidance and through food. This highlights the importance of the nutritionist in both processes.